Implementasi Aktivitas Komunikasi Pemasaran Digital Melalui Konten Media Sosial Museum Macan - Maharani, Andi Nabila (IPM2KPE, 2024)
This research aims to find out how digital marketing communication activities are implemented through the MACAN museum's social media content. This research uses a qualitative approach with descriptive methods. The research results found that the MACAN Museum divides the main types of content uploaded on Instagram into two types, namely visitation content related to ongoing exhibitions at the MACAN Museum or for example a list of artists currently exhibiting there, what kind of works are currently being exhibited. displayed and secondly there is also educational content which emphasizes educational aspects and knowledge of fine arts and design to the public. The conclusion of this research is that all communication activities carried out by the MACAN Museum are with the main aim of continuing to explore potentials on how to invite visitors from all levels of society and from various economic strata to attend and enjoy the MACAN Museum. Keywords: Communication Activities, Digital Content, Instagram, Social Media